THE EFFECT OF DIGITALIZATION OF TAXATION, TAX MORALE AND MODERNIZATION OF THE ADMINISTRATIVE SYSTEM ON TAXPAYER COMPLIANCE - Santioso, Linda; Daryatno, Andreas Bambang (Graduate Program of Universitas Tarumanagara, 2025)
This research aims to determine the effect of Tax Digitalization, Tax Morale and Administrative System Modernization on Taxpayer Compliance. The sample selection technique in this research used a convenience sampling technique. Data processing uses the Smart PLS program. The research results show that the administrative system modernization variable has a significant positive influence on taxpayer compliance, digitalization has a positive but not significant influence, while tax morale has a negative and insignificant influence. The implications of this research are that it is very important to maintain the security of taxpayer data and make it easier for taxpayers to access tax applications both when paying taxes and reporting taxes, which will increase taxpayer compliance because personal data is safe and makes it easier for taxpayers to carry out their tax obligations. Apart from that, with the DJP's plan to implement Coretax, which is one application used for all tax obligations, taxpayers will not be confused by the many tax applications currently used by taxpayers. The modernization of the tax system which continues to develop by following the technological era and taking advantage of current technological advances has a great influence on increasing tax compliance because it will be easier for taxpayers to access information and carry out their obligations as compliant taxpayers.